Jojo's bizarre adventure. Part 5, Golden wind. 8 - Araki, Hirohiko, 1960- (Shonen Jump manga., 2023)
Secco and Bruno Bucciarati are going head-to-head, quickly shifting between traveling underground and through zippers with their Stand powers in an attempt to gain the upper hand. Bucciarati has never faced a threat like this, but will the mysterious changes to his body and his enemy's overwhelming power crush him, or can he eke out a win just in time?